2020
DOI: 10.1080/21691401.2019.1596928
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: MiR-616 plays oncogenic role in hepatocellular carcinoma progression through suppressing PTEN expression and activating PI3K/AKT pathway

Abstract: 2020) MiR-616 plays oncogenic role in hepatocellular carcinoma progression through suppressing PTEN expression and activating PI3K/AKT pathway, Artificial Cells, Nanomedicine, and Biotechnology, 48:1, 728-734, ABSTRACT Aims: Given their regulatory roles in gene expression, microRNAs play an important role in tumorigenesis. The current study aimed to explore the function and the related mechanisms of miR-616 in hepatocellular carcinoma (HCC). Methods: The expression of miR-616 was detected using quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A close relationship between EMT and AKT signal pathway has been reported in the literatures [33]. In our study, the increased phosphorylated AKT was observed after DTX3 expression was knocked down.…”
Section: Discussionsupporting
confidence: 87%
“…A close relationship between EMT and AKT signal pathway has been reported in the literatures [33]. In our study, the increased phosphorylated AKT was observed after DTX3 expression was knocked down.…”
Section: Discussionsupporting
confidence: 87%
“…The invasion assay was revealed in 12‐well Transwell chambers 27 . Different concentrations of Sal‐A (0–50 µmol/L) were treated with NSCLC cells for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 miRNA are members of small noncoding RNA 19-25 nucleotides in length, the dysregulation of which leads to aberrant cell proliferation and malignant cell viability, ultimately resulting in cancer initiation or disease progression. 15,16 There is evidence that miR-125b-5p plays a protective role in multiple cancers and diseases such as bladder cancer, colorectal cancer, and nonalcoholic fatty liver disease. [17][18][19] In HCC, miR-125b-5p is downregulated both in vivo and in vitro, the upregulation of which significantly reduces HCC cell invasion and migration.…”
Section: Crosstalk Between Lncrna Dancr and Mir-125b-5p In Hcc Cell Progressionmentioning
confidence: 99%